The Effectiveness of Contextual Teaching Learning and Quantum Learning Models on Critical Thinking Skills and Self-Confidence of Fifth Graders - Wibowo, Sarwo Edi; Susilo, Susilo; Suminar, Tri (Educational Management, 2021)
This study aims to find out and analyze the improvement in critical thinking skills and self-confidence using contextual teaching learning (CTL) and quantum learning (QL) models for fifth graders. This study employed a quasi-experimental research design. The population of this research was fifth graders of SDN Mento involving 28 students, SDN Muntung 30 students, and SDN Canggal 28 students. These samples were selected using random sampling technique. The data in this study was obtained from tests and observation. The data analysis in this study included t-test by using SPSS 23.0 software. The results indicated that there was improvement in the critical thinking skills using CTL learning model with t-score 20.868 at sig. 0.000 as well as in the self-confidence with t score 2.845 at sig. 0.006. There was an improvement in the critical thinking skills using QL learning model with t score 3.061 at sig. 0.003 and in the self-confidence with t score 4.724 at sig. 0.000. The conclusion of this study is CTL and QL models are effective to enhance critical thinking skills and self-confidence of fifth graders.